The Interplay of Physical Activity and Emotional Well-being: A Cross-Sectional Study Among Physical Education Students - M Khoiri; Robyn Webber; Iryna Skrypchenko; Malena Bracken (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
Purpose of the study: This study aimed to examine the relationship between physical activity levels and emotional well-being among Physical Education students. Materials and methods: A cross-sectional quantitative study was conducted with 245 Physical Education students (mean age 20.4 ± 1.8 years, 58% male). Physical activity levels were assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), while emotional well-being was evaluated using the WHO-5 Well-being Index and the Positive and Negative Affect Schedule (PANAS). Data were analyzed using SPSS version 29.0 with correlation analysis and multiple regression modeling. Results: The study revealed a significant positive correlation between physical activity levels and emotional well-being (r = 0.67, p < 0.001). Students with high physical activity levels demonstrated significantly higher WHO-5 scores (M = 18.2 ± 3.1) compared to those with low activity levels (M = 12.4 ± 4.2, p < 0.001). Positive affect scores were significantly higher in the high activity group (M = 37.8 ± 6.2) versus the low activity group (M = 28.1 ± 7.4, p < 0.001). Multiple regression analysis indicated that physical activity accounted for 45% of the variance in emotional well-being scores (R² = 0.45, F(3,241) = 65.84, p < 0.001). Conclusions: This study provides evidence for a strong positive association between physical activity and emotional well-being among Indonesian Physical Education students. The findings suggest that promoting physical activity could be an effective strategy for enhancing emotional well-being in academic environments. These results have important implications for curriculum development and student support services in higher education institutions.